Studi Pengaruh Temperatur Evaporasi Terhadap Kinerja Siklus Rankine Organik Menggunakan Fluida Kerja R245FA Dan R515A - Dwinanto, Matheus Magnus (Universitas Nusa Cendana, 2023)
Nowadays, many power plants with the organic Rankine cycle (ORC) have been widely used in the world because they can utilize low temperature heat sources such as industrial waste heat, biomass, geothermal and solar energy. The working fluid for the ORC system must meet several physical property criteria including, environmentally friendly, non-flammable, non-toxic, and non-corrosive. Therefore, this study aims to analyze the effect of evaporation temperature on the energy performance of a standard organic Rankine cycle with a turbine power of 20 kW with working fluids R245fa and R515A. System simulation using Genetron Properties software with the condensation temperature maintained constant at 40oC and the evaporation temperature varied at 70 – 80oC. The results of this study show that increasing the evaporation temperature will greatly increase pumping power consumption but reduce the pressure ratio in the turbine and the thermal efficiency of the system. The pumping power used to circulate R515A is ±2.2 times higher than circulating R245FA but the thermal efficiency is ±9.75% higher.